Factors influencing the sexual drive of Russian women of reproductive age in the digital age - Anna I. Fedorova; Anna V. Kazakova; Svetlana M. Chechko; Gennadiy S. Kozupitsa; Irina E. Dufinets (IP Berlin A.V., 2023)
Aim. To assess the impact of age, number of sexual partners, having children, family income, and time spent with a smartphone or computer on the sexual drive of women of reproductive age in the era of information technology. Materials and methods. A study of the sexual drive of 79 women aged 18-35 in family (partner) relationships was conducted. The well-established international Female Sexual Function Index was used. Respondents also answered questions about some aspects of personality and social status. The results were evaluated using the methods of mathematical statistics: descriptive statistics, correlation, determination, and logit-regression analyses. Results. The intensity of sexual drive correlates with a woman's age, the number of sexual partners, and the family income. There was no correlation between the level of a woman's sexual drive and having children and the time women and their partners spend with computers and smartphones.